1989
DOI: 10.1017/s0033291700012381
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative computed tomographic study in schizophrenia: cerebral density and ventricle measures

Abstract: SynopsisTwenty-seven chronic schizophrenics and nineteen controls, all male, were evaluated by computed tomography (CT) scans. Lateral, third and fourth ventricles and cerebral density numbers were measured. In the schizophrenic patients there was a significant increase in third ventricle width. Ventricular Brain Ratio (VBR) and there were significantly higher densities of white matter in the right frontal and parietal region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Even within this limitation, it can still be said that, when compared with reports from developed countries, our findings show a lot of biological similarities. For instance, our finding of hyperdensity has been widely reported in studies from developed countries (Largen et aI., 1983(Largen et aI., , 1984Dewan et al, 1983;Rossi et al, 1989). In particular, similar to our findings, the report of Rossi et al, (1989) from Italy indicated that schizophrenics had significantly enlarged third ventricle and hyperdensity in the frontal and parietal regions.…”
Section: Discussionsupporting
confidence: 91%
“…Even within this limitation, it can still be said that, when compared with reports from developed countries, our findings show a lot of biological similarities. For instance, our finding of hyperdensity has been widely reported in studies from developed countries (Largen et aI., 1983(Largen et aI., , 1984Dewan et al, 1983;Rossi et al, 1989). In particular, similar to our findings, the report of Rossi et al, (1989) from Italy indicated that schizophrenics had significantly enlarged third ventricle and hyperdensity in the frontal and parietal regions.…”
Section: Discussionsupporting
confidence: 91%
“…However, current work suggests a renewed interest in the possibility of substantial parietal involvement in schizophrenia, and this work is implicitly embedded within a network paradigm. For example, recent studies using neuropsychological tests (Buchanan et al, 1994), psychophysiological methods (Buchsbaum et al, 1986), computed tomography (Rossi et al, 1989), magnetic resonance imaging (Harvey et al, 1993), and positron emission tomography (Cleghorn et al, 1989; Schroeder et al, 1994) have detected abnormalities in parietal structure or parietally mediated tasks in schizophrenia patients. Others have noted differential associations between schizophrenia symptoms and parietal deficits and/or levels of activation (Liddle, 1996; Tamminga, Buchanan, & Gold, 1998), with negative symptoms appearing to be functionally localized, in part, to the parietal cortex (Tamminga et al, 1998).…”
Section: Discussionmentioning
confidence: 99%